The Application of Learning Theory to Serial Murderor “You Too Can Learn to be a Serial Killer” - Hale, Robert L. (American journal of criminal justice, 1993)
Popular ideas concerning serial murder see these killings as an act committed by a deranged or irrational individual. This article contends that this is not the case, but that the killer is behaving in a manner which makes sense and is logical to the killer and is a response to some perceived wrong. The process through which this reponse occurs is detailed. The conclusion suggests that if serial murder is indeed a learned response then this response can be “unlearned” and the serial murderer can be restored to again function within society.